The Influence of Brand Ambassador on Purchasing Decisions for Wardah Products with Brand Image As An Intervening Variable at Indomaret Sigambal - Sri Hartati; Junita Lubis; Fauziah Hanum (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to determine the influence of Brand Ambassador on purchasing decisions of Wardah products with brand image as an intervening variable at Indomaret Sigambal. The data processing technique uses SPSS data analysis. The population in this study are customers or buyers at Indomaret in Sigambal Labuhanbatu. The sample collection technique used is probability sampling by leading to a random sampling incident, the number of samples used is 100 people who shop at Indomaret in Sigambal Labuhanbatu. The research concludes that brand ambassadors and brand image have an independent impact on purchasing decisions in terms of the results of the t-table comparison (0. 6777) is smaller than t-count, then brand ambassador and brand image have a positive impact on purchasing decisions. From the results of model 1 and model 2, it can be seen the magnitude of the direct impact given by the brand ambassador variable to purchasing decisions, namely: 0.308 and the indirect impact of brand ambassadors through brand image on purchasing decisions is 0.88. Based on the overall test, it can be seen that the brand ambassador and brand image have a simultaneous impact on purchasing decisions in terms of Sig 0.000 < 0.05 and based on the results of the f test, the brand ambassador and brand image have a simultaneous impact on purchasing decisions in terms of the calculated f value of 14.109 > from f table 3.94.